Reviews of cases of construction disputes in Malaysia and its relation with standard form of construction contract - Nee, Ting Sim; Nadarajan, Samuel; Whyte, Andrew (Trans Tech Publications, Switzerland, 2014)
In Malaysia itself, the construction industry has well governed the economic trend and providing the pathway towards modernization. Construction industry is a huge process that involves many activities in different phases and participation of various professions. The complexity of this industry has made it closely linked to disputes. There are always possibilities of dispute occurrence even when almost all projects are governed by their respective contracts. This study is initiated to find the relationship of standard forms of contract with construction disputes. The focus of this study will be on the construction disputes litigation cases in Malaysia reported to the Current Law Journal (CLJ) between year 1999-2009. The secondary data for this study is obtained from questionnaire survey distributed throughout Malaysia, which looks into construction dispute cases that were not referred to formal law journals. Research findings identified that all projects are governed by standard forms and even though the parameters causing construction dispute are actually monitored by the standard form itself, disputes are not declining or effectively resolved, and hence, making the standard forms as one of the the major causes of construction disputes.